The Influence of Product Quality, Reputation, and Trust on Purchasing Decisions at PT Semarak Konstruksi Batam - Lestari, Elisa Jayanti (Jurnal Ilmiah Manajemen dan Bisnis, 2024)
Digital marketing has revolutionized business-consumer interactions by providing unprecedented global reach and opportunities for influence. One notable example of this digital marketing transformation is the experience of "Somethinc" an Indonesian health and beauty products brand that expertly leveraged social media platforms to develop a strong brand identity and engage its target audience. This study investigates the diverse impacts of digital marketing on consumer behavior and business strategy. The study examines factors such as the effectiveness of digital platforms, product quality and price, which are expected to increase engagement, and the importance of data analysis in refining marketing approaches. Consumer purchase decisions are influenced by many factors, among which product quality and price are the most significant factors. Product prices reflect perceived value and quality, but the relationship between high prices and better quality is not always true, according to research. Location and product display also play an important role in purchasing decisions as the convenience of the location and visual experience in the store can increase consumer satisfaction. Good service from retailers also influences purchase decisions, with positive experiences increasing the likelihood of consumers to buy. Other research shows that while price is important, product quality also plays an equally important role in consumer decisions, often seeking a balance between the two to maximize satisfaction.